ANALISIS KEUNTUNGAN USAHATANI KELAPA DI KECAMATAN PADANGSIDIMPUAN BATUNADUA - Faisal Rahman (Quantitative Economics Journal, 2013)
As a traditional crop, coconut is a versatile plant (tree of life) and has an economic value that is good enough to be developed particularly in the context of community economic development. This study aims to determine the effect of input variables X1 (Wide Land), X2 (Labor Costs), and X3 (Cost Fertilizer) against the benefits of coconut farm in the district Padangsidimpuan Batunadua. Analytical model used is the Cobb-Douglas profit function with the help of Eviews v5.1 application.The results showed that simultaneous variables X1, X2, and X3 affect the benefits of coconut farm with F-stat is 1728,765. partially each variable as: X1 shows a positive and significant impact on profits by ilai tcount 53.811 and Prob. Of 0.000., X2 showed positive and significant influence on profits by the value of 21.503 tcount and Prob. Of 0.000., and X3 shows a negative influence to the value of -2.511 tcount and Prob. Of 0.0138. Furthermore, from the obtained values for the regression coefficient of 0.9834 X1 means any addition of land area per ha will increase the gain of 0.9864 rupiah per Ha, X2 of 0.9757 means that any additional labor costs / yields would increase the profit of  0.9575 rupiah and -0.0651 for X3 which means every addition 1 rupiah of fertilizer costs will reduce profits 0,0651 rupiah. From the analysis it can be concluded, that the coconut farm production and profits in Kecataman Padangsidimpuan Batunadua still can be improved by optimizing the use of variable inputs of fertilizer and land.